THE CONCEPT OF IKHTILĀF IN THE BOOK TAWḌĪḤ AL-AḤKĀM AND ITS RELEVANCE TO MARRIAGE LAW IN INDONESIA - Parlindungan Simbolon; Hidayatullah Ismail; Hendri K (Hukum Islam, 2023)
The Difference of moeslim scholar’s opinion in determining furu’iyah laws will always occur in every era. It can be caused by the difference in understanding and methods that are used to determine the law. Sometimes, these differences trigger conflict among society,  In order to avoid conflict of the society, it needs an appropriate approach to compromise (al-jam'u) these differences. Among the contemporary scholars who discuss this issue is 'Abdullah bin 'Abdurraḥmān al-Bassām in the book Tawḍīḥ al-Aḥkām. Various kinds of ikhtilaf issues are raised by al-al-Bassam in this book. The problem in this research is how is the concept of ikhtilāf in the book of Tawḍīḥ al-Aḥkām and its relevance to marriage law in Indonesia? This study aims to examine issues of ikhtilāf in the Kitab al-Nikah in the book of Tawdih al-Ahkam and how the al-Bassām method solves them and their relevance to marriage law in Indonesia. This research is a qualitative descriptive study involving the documentation method. The data in this study were analyzed using the content analysis method. The results of this study indicate that there are six problems of ikhtilaf related to marriage in the book of Tawdih al-Ahkam. Al-Bassam solved the problem by using three methods, namely 'Ard al-Aqwal, Munaqasyah al-Adillah and al-Tarjih. The tarjih performed by al-Bassam is in accordance with the marriage law in Indonesia as stipulated in the Compilation of Islamic Law.